Vital Statistics for Leading Countries in COVID-19 Cases - Singh, Zorawar (Journal of Diseases, 2020)
Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus and the overall number of the COVID-19 cases is increasing worldwide. As on 24th March, 2020, China, Italy and United States were found to be the countries with maximum number of reported cases. China seemed to manage this outbreak with only 3,281 deaths for 81,218 cases with a death rate of 0.040 and a recovery record of 73,650 patients. The present review emphasizes the comparative patterns with which this pandemic spread in the above mentioned three countries. Paper also discusses total cases, daily recorded cases and total deaths of patients with daily death records. Conclusively, COVID-19 is affecting the population globally at a very rapid rate and should be dealt with maximum efforts by all the countries.